Thoughts on physical education in the scientific creativity of Polish pedagogues and physicians of the modern era (1492-1918) - Kaźmierczak, Arkadiusz (Journal of Education, Health and Sport, 2017)
In the modern era (1492-1918), physical activity functioning on the basis of Polish thought about upbringing appeared to be vague. The care for high level of physical fitness and good health in the educational concepts of this era resulted from the need to adapt the education system to the progress of science and social transformations. The pedagogues and physicians in a remarkably mature way perceived the universal values of physical activity, the cognition of which by means of science has created the possibility of understanding the educational and health sense of physical exercises and their place in the education system of children and youth. In extensive writing , as well as speeches presented at conferences and congresses of this period, we find the theoretical and methodical justification for the need for physical activity of the young generation. This publication, which is of illustrative nature, is the author's recognition of the achievements of these known and less known pioneers of Polish thought about physical education, to whom representatives of contemporary scientific disciplines dealing with upbringing refer.